Kenneth Burke's Weed Garden : Refiguring the Mythic Grounds of Modern Rhetoric - Jensen, Kyle (Penn State University Press, 2022)
Since its publication in 1950, Kenneth Burke's A Rhetoric of Motives has been one of the most influential texts of theory and criticism. Critics have discovered in its pages concepts that reveal new dimensions of human motivation. And yet, despite its obvious genius, critics have interpreted A Rhetoric of Motives as a collection of provocations rather than a systematic treatment of rhetoric.In this book, Kyle Jensen argues that the coherence in Burke's thought has yet to be fully appreciated. Drawing on unpublished drafts and voluminous correspondence, he reconstructs Burke's drafting and revision process for A Rhetoric of Motives as well as its recently discovered second volume, The War of Words. Jensen's extensive archival analysis reveals that Burke relied on the concept of myth to draw together the loose ends in his argument. For Burke, all general theories of rhetoric are formed and structured using mythic images and terms.By exploring what Burke added and omitted, and by putting his writing process into the context of daily life after the Second World War--including Burke's attempts to clear the weeds from his Andover farm--Jensen sheds new light on the key problems that Burke encountered and the methods he used to overcome them. Kenneth Burke's Weed Garden is essential for those who study Burke and the tradition of modern rhetoric that he helped found.